Assessing Climate-Related Financial Disclosure Based on The TCFD Framework at Padjadjaran University - Ridha Fiharani Abdillah; Arie Pratama; Annisa Nabila Hasan (Pustaka Digital Indonesia, 2026)
The urgency of this research is to assess climate-related financial disclosure based on the Task Force on Climate-related Financial Disclosures at Universitas Padjadjaran to ensure transparency, effective risk mitigation, and institutional readiness in addressing climate change impacts .Climate change creates various risks and opportunities that affect not only the business sector but also public institutions, including higher education institutions. Climate-related risks may influence operational sustainability, asset management, and long-term financial stability, thereby requiring a structured disclosure framework to support transparent and systematic reporting. This study aims to develop a climate-related financial disclosure framework for Padjadjaran University based on the recommendations of the Task Force on Climate-related Financial Disclosures (TCFD). This study employs a qualitative approach using an exploratory and action research design, with Padjadjaran University as the unit of analysis. Data were collected through document analysis and semi-structured interviews with stakeholders involved in sustainability management, selected using purposive sampling. The instruments included document review guidelines and interview protocols, and the data were analyzed using qualitative content analysis by mapping findings into the four core pillars of the TCFD framework: governance, strategy, risk management, and metrics and targets. The results indicate that although various sustainability initiatives have been implemented, climate-related information remains fragmented and has not been integrated into a structured disclosure framework. This study proposes a TCFD-based disclosure format that integrates governance, strategy, risk management, and measurable indicators. The findings provide practical implications by offering a structured guideline to improve transparency, support risk-based decision-making, and strengthen institutional accountability, and the framework can be adapted by other higher education institutions in developing more comprehensive climate-related reporting practices. The urgency of this research is to assess climate-related financial disclosure based on the Task Force on Climate-related Financial Disclosures at Universitas Padjadjaran to ensure transparency, effective risk mitigation, and institutional readiness in addressing climate change impacts .Climate change creates various risks and opportunities that affect not only the business sector but also public institutions, including higher education institutions. Climate-related risks may influence operational sustainability, asset management, and long-term financial stability, thereby requiring a structured disclosure framework to support transparent and systematic reporting. This study aims to develop a climate-related financial disclosure framework for Padjadjaran University based on the recommendations of the Task Force on Climate-related Financial Disclosures (TCFD). This study employs a qualitative approach using an exploratory and action research design, with Padjadjaran University as the unit of analysis. Data were collected through document analysis and semi-structured interviews with stakeholders involved in sustainability management, selected using purposive sampling. The instruments included document review guidelines and interview protocols, and the data were analyzed using qualitative content analysis by mapping findings into the four core pillars of the TCFD framework: governance, strategy, risk management, and metrics and targets. The results indicate that although various sustainability initiatives have been implemented, climate-related information remains fragmented and has not been integrated into a structured disclosure framework. This study proposes a TCFD-based disclosure format that integrates governance, strategy, risk management, and measurable indicators. The findings provide practical implications by offering a structured guideline to improve transparency, support risk-based decision-making, and strengthen institutional accountability, and the framework can be adapted by other higher education institutions in developing more comprehensive climate-related reporting practices.